Blow-up time of solutions to a class of pseudo-parabolic equations - Zhou, Jun; Wang, Xiongrui (Comptes Rendus. Mécanique)
In this paper, we study the Dirichlet problem for a semilinear pseudo-parabolic equation. By using the energy estimates and ordinary differential inequalities, we studied the upper and lower bounds of blow-up time of the solutions. The results of this paper extend and complete the results on this model.